Effect of metformin monotherapy and dual or triple concomitant therapy with metformin on glycemic control and lipid profile management of patients with type 2 diabetes mellitus - Lin, Yan-Yu; Weng, Shuen-Fu; Hsu, Chung-Huei; Huang, Chen-Ling; Lin, Yu-Pei; Yeh, Min-Chun; Han, A-Young; Hsieh, Yu-Shan (Frontiers in Medicine, 2022)
Background In this study, we aimed to compare the effects of metformin-based dual therapy versus triple therapy on glycemic control and lipid profile changes in Taiwanese patients with type 2 diabetes mellitus (T2DM). Methods In total, 60 patients were eligible for participation in this study. Patients received at least 24 months of metformin monotherapy, dual therapy, or triple therapy with metformin plus linagliptin (a dipeptidyl peptidase 4 (DPP-4) inhibitor) or dapagliflozin (a sodium-glucose cotransporter-2 (SGLT2) inhibitor). Blood samples were collected from each patient, followed by evaluation of changes in their blood glucose control and lipid profile-related markers. Results A combination of metformin and DPP4 and SGLT2 inhibitor therapy more effectively reduced low-density lipoprotein cholesterol (LDL-C) (p = 0.016) than metformin monotherapy. A combination of metformin and DPP4 and SGLT2 inhibitor therapy more effectively improved total cholesterol (Chol, p = 0.049) and high-density lipoprotein cholesterol (HDL-C) than metformin monotherapy (p = 0.037). Metformin plus linagliptin dual therapy was more effective than metformin monotherapy in reducing glycosylated hemoglobin (HbA1C, p = 0.011). Patients who received a combination of linagliptin and empagliflozin showed a significant reduction in their fasting blood glucose (p = 0.019), HbA1c (p = 0.036), and Chol (p = 0.010) compared with those who received linagliptin dual therapy. Furthermore, patients who received metformin plus dapagliflozin and saxagliptin showed significantly reduced Chol (p = 0.011) and LDL-C (p = 0.035) levels compared with those who received metformin plus dapagliflozin. Conclusion In conclusion, dual therapy with metformin and linagliptin yields similar glycemic control ability to triple therapy. Among metformin combination triple therapy, triple therapy of empagliflozin and linagliptin might have a better glycemic control ability than dual therapy of linagliptin. Moreover, Triple therapy of dapagliflozin and saxagliptin might have a better lipid control ability than dual therapy of dapagliflozin and saxagliptin might have a better lipid control ability than dual therapy of dapagliflozin.